Metode Problem Base Learning (PBL) dalam Peningkatan Pemahaman Fikih Kontemporer - Samsul Arifin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2019)
method Problem Based Learning is one type of learning method based on cognitive psychology that assumes that learning is a process of changing behavior thanks to experience. Judging from the philosophical aspects of the function of the school as an arena or container to prepare students to be able to live in society, then this method is a possible and very important strategy to develop. Problem solving is seen as a process to find a combination of a number of rules that can be applied in an effort to overcome a new situation. So that this learning model as a way of presenting lesson material by making the problem as the starting point of the discussion to be analyzed and synthesized in an effort to find a solution to the problem being studied. Moreover, the use of the right method and approach will produce an understanding that can be tested to be used as a benchmark in conducting the next learning process, especially if using a problem-based approach in conducting a religious study by raising problems. At the same time, deliberation together in order to obtain answers to the problem with the classic books or the latest fatwas as a reference of the opinions put forward. In addition, the use of problem-based methods also has advantages over other types of learning methods, such as lecture and question and answer methods. Especially in solving various problems in the field of Masailul Fiqh or Bahtsul Masail.